2023
DOI: 10.3390/ijms24065305
|View full text |Cite
|
Sign up to set email alerts
|

Sessile Trichomes Play Major Roles in Prey Digestion and Absorption, While Stalked Trichomes Function in Prey Predation in Byblis guehoi

Abstract: Carnivorous plants in the genus Byblis obtain nutrients by secreting viscous glue drops and enzymes that trap and digest small organisms. Here, we used B. guehoi to test the long-held theory that different trichomes play different roles in carnivorous plants. In the leaves of B. guehoi, we observed a 1:2.5:14 ratio of long-stalked, short-stalked, and sessile trichomes. We demonstrated that the stalked trichomes play major roles in the production of glue droplets, while the sessile trichomes secrete digestive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Due to their rarity, two genera of carnivorous plants within Lamiales with an independent origin of carnivory, Byblis and Philcoxia , remain also a totally unexplored group of carnivorous plants in regard to digestive physiology. It was suggested that Byblis resembles Roridula and relies on digestive mutualisms ( Ellis and Midgley 1996 ), but Li et al . (2023) recently documented protease activity in Byblis guehoi , which makes Byblis an interesting object for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their rarity, two genera of carnivorous plants within Lamiales with an independent origin of carnivory, Byblis and Philcoxia , remain also a totally unexplored group of carnivorous plants in regard to digestive physiology. It was suggested that Byblis resembles Roridula and relies on digestive mutualisms ( Ellis and Midgley 1996 ), but Li et al . (2023) recently documented protease activity in Byblis guehoi , which makes Byblis an interesting object for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Cuticle discontinuities in carnivorous plant glands are easily detected using vital dyes, e.g., an aqueous solution of neutral red or methylene blue [24,31,36,37,40]. Moreover, these cuticle discontinuities in carnivorous plant glands allow intact cells to be penetrated by dyes such as DiOC 6 and styryl dye FM4-64, thereby making it possible to visualize the organelles and membranes, as was shown by Płachno et al [41], Lichtscheidl et al [44], and Li et al [45]. Thus, these cuticle discontinuities make the cells of the carnivorous plant glands an excellent research model.…”
Section: Introductionmentioning
confidence: 95%